Sejarah Intelektual Ulama Nusantara: Reformulasi Tradisi di Tengah Perubahan - Agus Iswanto (Jurnal Lektur Keagamaan, 2013)
This article is written based on book-review of Ulama dan Kekuasaan: Pergumulan Elite Muslim dalam Sejarah Indonesia, written by Jajat Burhanudin. This book cloncludes that what is now seen as a social and cultural capital of ulama--which makes them able to reconstruct, reformulate, and modify traditions—is actually the result of the accumulation of a long historical process in the history of Indonesia. After presenting summary of this book, the article analyses the perspective of historiography used, originality of historiography seen from sources, and disscuses ulama in the light of power and knowledge relation. Keywords: Indonesian ulama, intellectual history, originality of historiography, power-knowledge relation.